Episodic facial edema as a presentation of pleomorphic adenoma – case report - Martins F; Pereira E (Galicia Clínica, 2016)
Peripheral edema is a common complaint in the emergency department. Isolated facial edema is usually associated with angioedema or venous obstruction but the actual cause of obstruction might not be straightforward. The authors present a case of a 56 year old woman who presented to the emergency department with a 2 year history of episodic facial and right upper limb edema, with no palpable masses or any physical examination alterations. Further study revealed a right parapharyngeal mass suggestive of a pleomorphic adenoma. The patient underwent surgery with no complications. Follow-up at one year with no evidence of recurrence. The approach to the patient with isolated facial edema is always challenging. The immediate differential diagnosis usually relies on angioedema or venous thrombosis. Parapharyngeal space tumors are rare and usually present as an intraoral or cervical mass which did not happen in our case. The facial edema as the major complaint can be explained by the tumor growth compressing adjacent structures along with the internal jugular vein thrombosis. Parapharyngeal space tumors are rare and can be quite challenging especially when the patient presents with peculiar symptoms. This case highlights a peculiar and rare presentation of a tumor and the importance of clinical thinking in a patient with exquisite complaints.